The Discrepancy between Subjective and Objective Measures of Sleep in Older Adults Receiving CBT for Comorbid Insomnia. Issue 10 (20th December 2012) - Lund, Hannah G.; Rybarczyk, Bruce D.; Perrin, Paul B.; Leszczyszyn, David; Stepanski, Edward
<x xml:space="preserve">Abstract</x> Objective To examine the effect of cognitive‐behavioral therapy for insomnia (CBT‐I) on the underreporting of sleep relative to objective measurement, a common occurrence among individuals with insomnia. Method Pre‐treatment and post‐treatment self‐report measures of sleep were compared with those obtained from home‐based polysomnography (PSG) in 60 adults (mean age = 69.17; 42 women) with comorbid insomnia. The self‐report data were published previously in a randomized controlled trial demonstrating the efficacy of CBT‐I compared with a placebo treatment. Results Self‐report measures significantly underestimated sleep at pre‐treatment and CBT‐I led to a correction in this discrepancy. There were no significant changes in PSG after CBT‐I. Path analysis showed that an increase in an objective proxy measure of sleep quality (i.e., decreased stage N1 sleep) after CBT‐I was significantly related to improvements in self‐report of sleep, with full mediation by reductions in discrepancy. Conclusions This is the first CBT‐I outcome study to analyze discrepancy changes and demonstrate that these changes account for a significant portion of self‐report outcome. In addition, improved sleep quality as measured by a decrease in percentage of stage N1 sleep following treatment may be one mechanism that explains why sleep estimation is more accurate following CBT‐I.